Leptospiral adhesins: from identification to future perspectives - Surdel, Matthew C.; Coburn, Jenifer (Frontiers in Microbiology, 2024)
Leptospirosis is a significant zoonoses worldwide, with disease severity ranging from a mild non-specific illness to multi-organ dysfunction and hemorrhage. The disease is caused by pathogenic bacteria of the genus Leptospira, which are classified into pathogenic and saprophytic clades. Bacterial binding to host molecules and cells, coordinated by adhesin proteins, is an important step in pathogenesis. While many leptospiral adhesins have been identified, the vast majority have not been characterized in vivo. Herein, we present an overview of the current methodologies and successes in identifying adhesins in Leptospira, including known biological roles in vivo. We will also identify and discuss potential areas for future research.